Aktualizacja, fragmentaryzacja, trwanie – próba opisu perspektyw czasowych współczesnego dokumentu - Boratyn, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article describes certain changes that have taken place over the last several years in the temporal perspective found in documentary films. Humanity’s current technological and media environment are influencing the documentary’s content and means of expression. They express a “universal present”, as Mirosław Przylipiak has pointed out, under the influence of television, and the former dominance of statements addressed to the camera gave way to looks into the past. At present, the documentary is once again shifting its orientation toward a strictly defined and changing form of the present. Time in the temporally non-linear works commonly found among contemporary documentaries has become fragmented and individualized. There is also a tendency in non-fiction works to strive for immersion – focusing on the experience of time rather than the telling of a story.